Coccolithophore distributions of the North and South Atlantic Ocean. (September 2019) - Balch, William M.; Bowler, Bruce C.; Drapeau, David T.; Lubelczyk, Laura C.; Lyczkowski, Emily; Mitchell, Catherine; Wyeth, Amy
Abstract: We present average coccolithophore and associated biogeochemical results from ten Atlantic Meridional Transect (AMT) cruises between 50 o N-50 o S, results that show a number of unique observations across this massive data set. Lowest concentrations of coccolithophores were consistently found in equatorial waters. Highest concentrations of coccolithophore cells and coccoliths were associated with temperate, sub-polar environments. Concentrations of detached coccoliths were dispersed to ∼300m depth and show low inter-cruise variance. Coccolithophore cell concentrations in the subtropics remain highest at < 200m depth in the S. Atlantic and 100m in the N. Atlantic, near the 26.5 to 27 sigma-theta (σθ ) isopycnal, within the Subantarctic Mode Water (SAMW). Diversity and species richness of coccolithophore cells was greater than for the detached coccoliths and generally greater in surface populations than in the deep chlorophyll maximum (DCM). Placolith-bearing coccolithophore species dominated over the umbelliform and floriform coccolithophore groups in surface waters of the Southern Ocean at 50 o S, as well as the DCM from 50 o S to the equator. The DCM was strongly associated with the σθ, of ∼27 kg m -3, coincident with the top of the nitracline, within the SAMW. Concentrations of coccolithophore cells and detached coccoliths were much less related to the density field than chlorophyll was. Highest integrated euphotic coccolith concentrations were observed when the integrated POC:chlorophyll ratio was highest. PIC:POC ratios increased with depth and approached maximum values near the top of the nitracline. Great Calcite Belt waters (upper 300m) showed biogenic silica:particulate inorganic carbon ratios (BSi:PIC) >1 while all other waters showed BSi:PIC ratios <1. Peaks in PIC and BSi were observed within, and above the SAMW, in waters with low phosphate and silicate concentrations. The results of this study suggest that coccolithophore-rich SAMW in the Southern Ocean is being conditioned after its formation, such that by the time it upwells in the Atlantic equatorial region, the water is no longer conducive to coccolithophore growth. Highlights: Atlantic coccolithophores show a consistent abundance minimum in equatorial waters. Deep euphotic coccolithophores are associated with Sub-Antarctic Mode Water (SAMW). Maximum coccolithophore concentrations are found in north and south temperate waters. Concentrations of biogenic silica nonetheless exceed PIC in the Great Calcite Belt. Coccolithophore diversity is over double that for their detached coccoliths.